Condition assessment and analysis of a reinforced concrete building in India: a case study. Issue 4 (30th July 2021) - Anand, N; Andrushia, Diana; Paul, Daniel; Arulraj, Prince
Abstract : Structural concrete is a composite material commonly used for the construction of buildings and structures. Reinforced concrete members should be designed for strength, as well as durability. The long service life of the entire structure depends on the durability of concrete. The quality of construction materials, cover to the concrete, exposure conditions and quality of concrete are some of the key factors that affect the durability of concrete. Also, water penetrates easily and finds its way inside concrete through connected pores if the degree of compaction is not proper. Stagnant rainwater in the roof or a high water table may pave the way for the entry of water. The entry of water into structural concrete mainly causes corrosion, thereby reducing the strength of structural elements and initiating the spalling of concrete. A case study based on diagnosis, non-destructive testing and failure analysis of a reinforced concrete building in India is presented. The rehabilitation measures to be undertaken to maintain the service life of the building are also presented.